The relationship between college athletes' health literacy and COVID-19 anxiety levels - Sinan Uğraş; Ahmet E. Sağın; Ömer Karabulut; Gökmen Özen (Physical Education of Students)
Background and Study Aim. Health literacy is the ability to access health information, understand, evaluate and apply health information. The health literacy of athletes may be determinant in the understanding of the COVID-19 pandemic process and in the level of the impact of this health-related anxiety factor. Therefore, the aim of this study is to examine whether there is a relationship between college athletes' COVID-19 anxiety levels and their health literacy levels during the COVID-19 pandemic.